L’assurance des risques politiques - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1983)
ln July 1980, Assurances published two articles on political risks insurance, one of which appeared in the research and development section. The present article reviews the various publications on this question and provides a list of articles on the subject appearing from 1980 to 1982. Those with an asterisk have been used in the preparation of the present article.